THE FOUNDATIONS OF PHYSICAL EDUCATION IN THE CIVILIZATIONS OF SUMER BABYLON AND ASSYRIA-AN ANALYTICAL STUDY IN ANCIENT MESOPOTAMIAN EDUCATIONAL THOUGHT - Mohamed Ahmed Hassan (Proximus Journal Publishing, 2025)
This research examines the intellectual and educational principles that shaped the concept of physical education in the civilizations of Sumer Babylon and Assyria as the earliest human attempts to achieve harmony between the body the mind and the spirit within an integrated educational system that aimed to build a balanced individual in strength character and moral awareness The study seeks to uncover the philosophical and social ideas that influenced physical practices in Mesopotamia by analyzing cuneiform writings royal inscriptions and archaeological findings that carry symbolic and ritual meanings related to movement and education The descriptive analytical method was used to compare the forms of physical activity found in these three civilizations and to connect them with modern concepts of education through a historical perspective The findings reveal that ancient Mesopotamian thought did not treat physical activity as entertainment but as a formative process for developing discipline loyalty and readiness for service to the community while enhancing the sense of unity and belonging The research concludes that physical education was an essential part of a wider cultural and religious framework that linked obedience strength and cooperation It recommends revisiting the Mesopotamian heritage of physical education and applying its principles in the training of teachers and coaches as this legacy represents a deep cultural foundation for understanding the evolution of human educational thought in its moral physical and social dimensions
Keywords: Physical Education; Sumer; Babylon; Assyria